Rancang Bangun Website Program Studi Bisnis Digital Politeknik Negeri Banyuwangi - Ferdiansyah, Erik; Suardinata, I Wayan; Ratri, Indira Nuansa; Kristanto, Sepyan Purnama; Wibowo, Galih Hendra (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
The Digital Business Study Program at Banyuwangi State Polytechnic aims to equip Development of an Information System for the Digital Business Study Program Using Laravel Framework and Rapid Application Development (RAD) Approach This study aims to enhance the documentation and sustainability of the Digital Business Study Program at Politeknik Negeri Banyuwangi through the development of a Laravel-based information system, replacing the previous WordPress platform. The new system is designed using the Rapid Application Development (RAD) approach to ensure swift, flexible, and stakeholder-oriented development. Black-box testing indicates that the system successfully manages login processes, user data, and content with a 100% success rate. The system implementation results in a 25% improvement in data integrity, a 30% reduction in processing time for managing news and curriculum, and an 85% increase in user satisfaction based on a survey of 50 respondents, including students and lecturers. The primary contribution of this study is the introduction of the RAD approach in the context of academic information system development, which can serve as a reference for similar systems in other educational institutions. The system not only provides comprehensive information on curriculum, program activities, new student admissions, student achievements, and news but also fosters greater public engagement with the Digital Business Study Program through a responsive and user-friendly interface.